Management of Fishermen's Sea Products in the Perspective of Regional Autonomy - Boemiya, Helmy; Nugroho, Lucky Dafira; Firdiyansyah, Erik Edwar (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Sumenep Regency has great marine management potential. Because Sumenep Regency's position is surrounded by sea, there are many benefits for the Regional Government of Sumenep Regency as well as for its people. With good management, it will produce multiple profits for regional income. One of them is for cultivation activities, either at sea or on land. Apart from the good water conditions, the coastal area has a suitable substrate for cultivation such as seaweed, fish, and shrimp cultivation. This research focuses on the role of local governments in managing fishermen's marine products, starting from catching fish or cultivating fish in the sea, then there is fish that is sold directly either at auction or directly to markets and buyers or middlemen, as well as fish that are processed in such a way as ingredients. or processed products and marketed to the public, so that they have added value, not just catching fish and selling them, but thinking about how to innovate. This requires the role of the Regional Government through related agencies in changing the mindset and managing fishermen's marine products so that they have value and high selling prices. This research aims to understand and analyze the obligations of local governments in managing fishermen's marine products as well as understanding, analyzing, and formulating appropriate regulations for managing fishermen's marine products in Sumenep Regency. This research is empirical research that examines social phenomena and realities in society. This research was carried out by analyzing the problem of marine product management as an effort to improve the welfare of fishermen’s from the perspective of regional autonomy. In fact, with regional autonomy, the role of regional government is very important for fishermen’s to be competitive and independent in solving fishermen's welfare problems. The results of this research show that there is a mindset of fishermen’s who are still just catching and selling, then in terms of regional level regulations in Sumenep Regency, there are no regional regulations that provide legal certainty regarding the protection and empowerment of fishermen’s, especially the management of fishermen's marine products.